Benefit of Clofibrate on indirect hyperbilirubinemia in newborn - Baha D. Moohy Alosy (College of Pharmacy / Mustansiriyah University, 2018)
Background: hyperbilirubinemia develop in all newborns and resolves within the first several weeks after birth. Clofibrate is planned for management of indirect hyperbilirubinemia Aim: to evaluate Benefit of Clofibrate on indirect hyperbilirubinemia in newborn. Patients and Methods: this is a case- control study of 100 neonates on clofibrate and 100 neonates control groups, both with jaundice enrolled in fifty sex months from June 2008- March 2013 in the Tikrit hospital and personal doctor's office ,Clofibrate group received clofibrate 100mg/kg.Evaluation of TSB reduction at different intervals regarding admission day,after 12-hr, 24-hr and4-day compare with control Results:The12-hr,24-hr,4-days reduction in TSB of clofibrate group were higher19.74±1.72mg/dl , 15.49±1.16mg/dl, 10.4±1.7mg/dL than in control group 17.11 ± 2.02 mg/dL, 16.09± 1.96mg/dL, 13.6±1.52mg/dL respectively with overall significant (P = .031944) The diminished need for phototherapy (P = 0.0198) and hospitalization time (P = 0.025) in clofibrate group were significantly important compare with control group Conclusion: Clofibrate (100mg) solitary dose used in neonates safely because decreasing bilirubin additionally reduce phototherapy , hospitalization time in neonates appeared within 24 hr and full action of clofibrate appeared between 24hr up to 96 hr.